Exploring The Types and Pragmatic Functions of Fillers in University Podcast Discourse - Muhammad Fatah Attamimi; Sri Wuli Fitriati; Yuliati (PROJECT (Professional Journal of English Education), 2026)
This study explores the role of fillers used by international students in a spontaneous communication setting through a podcast interview at Universitas Negeri Semarang. The study aims to classify the types as well as to analyze the pragmatic functions of fillers as used by the students during the podcast, utilizing Rose’s (1998) filler classification and Stenström’s (1994) filler function theories as the framework. A descriptive qualitative single case study approach was employed for the study, collecting extensive transcription data from the entirety of the podcast which consisted of six Denish students as the key participants. The collected data was then analyzed thoroughly using content analysis method, focusing on each student’s utterances in order to identify the fillers and their meaning in the context of the podcast. The findings show that lexicalized filler is the more dominant type used by the students, occurring 197 times from an accumulation of 274 fillers throughout the podcast. In addition, the most used pragmatic function of filler is the hesitation device. The findings highlight that international students strongly rely on lexicalized fillers to manage spontaneous communication and maintain the flow of conversation during a podcast interview.